ROADMAP AND SUSTAINABLE ISLAMIC BOARDING SCHOOL BUSINESS RESILIENCE MODEL BASED ON A POST-PANDEMIC COVID-19 GREEN ECONOMY IN WEST JAVA - Uus Rustiman (International Journal of Economy, Education and Entrepreneurship, 2023)
2022 is a momentum for Indonesia to focus more on a green economy. As the host of the G20, Indonesia is mandated to support three programs as a main priority: digital transformation, green economy, and energy transition. Several national policies and regulations have been directed to support a green economy but still need to be optimized, especially those related to empowering MSMEs, including Islamic Boarding School Business Units that are environmentally friendly. Businesses managed by Islamic boarding schools are growing in Indonesia, including in West Java, 9,167 or 31.8% of all Islamic boarding schools in Indonesia. However, the Covid-19 pandemic has caused the Islamic Boarding School (Pesantren) economy and business to not develop in the past year. For this reason, it is necessary to conduct research in the form of a roadmap and sustainable business resilience model in Islamic boarding schools based on a green economy. This model combines secondary data processing in the form of a literature review and primary data in the form of empirical observations in several pesantren that have survived and developed during the Covid-19 pandemic, especially those that support green economic aspects. The implementation model will be developed in several regions and cities